The macrophage: a key player in the pathophysiology of peripheral neuropathies - Msheik, Zeina; El Massry, Mohamed; Rovini, Amandine; Billet, Fabrice; Desmoulière, Alexis (Journal of neuroinflammation, 2022)
Macrophages are present in all mammalian tissues and coexist with various cell types in order to respond to different environmental cues. However, the role of these cells has been underestimated in the context of peripheral nerve damage. More importantly, macrophages display divergent characteristics, associated with their origin, and in response to the modulatory effects of their microenvironment. Interestingly, the advent of new techniques such as fate mapping and single-cell transcriptomics and their synergistic use has helped characterize in detail the origin and fate of tissue-resident macrophages in the peripheral nervous system (PNS). Furthermore, these techniques have allowed a better understanding of their functions from simple homeostatic supervisors to chief regulators in peripheral neuropathies. In this review, we summarize the latest knowledge about macrophage ontogeny, function and tissue identity, with a particular focus on PNS-associated cells, as well as their interaction with reactive oxygen species under physiological and pathological conditions. We then revisit the process of Wallerian degeneration, describing the events accompanying axon degeneration, Schwann cell activation and most importantly, macrophage recruitment to the site of injury. Finally, we review these processes in light of internal and external insults to peripheral nerves leading to peripheral neuropathies, the involvement of macrophages and the potential benefit of the targeting of specific macrophages for the alleviation of functional defects in the PNS. Graphical Abstract